Management platform for cooperative transport systems - Seabra, Lucas (2022)
The rapid evolution of technology led to increased research in domains such as smart devices. As a result, the Internet of Things technology has expanded rapidly and is being used to solve challenges needing vast quantities of data from many devices. With this, the Smart City concept became more popular with the goal of establishing a healthy ecosystem in which the functioning of the city is enhanced. The European Commission subsequently adopted Cooperative Intelligent Transport Systems (C-ITS), which enables road users and traffic controllers to share information and coordinate their actions. In addition, the Institute of Telecommunications (IT) group has placed and continues to install Road Side Units (RSUs) on Portuguese roads. These intelligent devices may have radars, cameras, or other elements that aid in determining traffic patterns. This dissertation emerges in the context of offering a C-ITS platform capable of addressing the demands of IT researchers and delivering feedback to them and regular road users on traffic behavior or alerts. For the development of a proof-of-concept system, a user-centered design approach was adopted, beginning with the identification of target users and the collection of key requirements generated from usage scenarios. The developed system implemented a micro-service architecture. The proof-of-concept is composed by several modules responsible for handling the camera stream, admin privileges, radars data, creation of alerts and several streams of data. The presented system showed to be capable of providing useful information to the users and administrators. By using the developed platform, users may see a collection of information as charts, interact with the RSUs installed on the roadways, generate and display alerts, and interact with the camera’s live stream.